Search
Ask a question
0

f(x)=5-3x f(t)+f(-2)=eval and simplify

f(X)=5-3x f(t)+(-2)=eval and simplefy

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Jason S. | My goal is the success of my students. Knowledge-Patience-HonestyMy goal is the success of my students. K...
4.9 4.9 (115 lesson ratings) (115)
0
f(t) means to substitute t in for x in f(x).  f(-2) means to substitute -2 in for x in f(x)
 
f(t) = 5-3t
 
f(-2) = 5-3(-2) = 5+6 = 11
 
f(t) + f(-2) = (5-3t) + 11  = 5-3t+11 = 5+11-3t = 16 - 3t